Motivasi Kepesertaan Mandiri BPJS di Era Universal Health Coverage Jaminan Kesehatan Nasional - Anita Dahliana (Direktorat Penerbitan dan Publikasi Ilmiah Universitas Surabaya, 2019)
Abstract. This research was conducted to determine the motivation of BPJS Health participants as independent participants. In this study, researchers used a motivational theory developed by Clayton Alderfer with three indicators namely Existence, Relatedness and Growth with a descriptive quantitative research approach with non-random sampling using a purposive method using conditions in selecting respondents ie respondents were outpatients in Specialist Poly Wiyung Hospital, Surabaya. The selected respondents were 43 people.The results of this study were the discovery of community motivation as independent health insurance participants.